2012
DOI: 10.1186/1471-2458-12-733
|View full text |Cite
|
Sign up to set email alerts
|

The injury mortality burden in Guinea

Abstract: BackgroundThe injury mortality burden of Guinea has been rarely addressed. The paper aimed to report patterns of injury mortality burden in Guinea.MethodsWe retrieved the mortality data from the Guinean Annual Health Statistics Report 2007. The information about underlying cause of deaths was collected based on Guinean hospital discharge data, Hospital Mortuary and City Council Mortuary data. The causes of death are coded in the 9th International Classification of Diseases (ICD-9). Multivariate Poisson regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…If this profile is superimposed on that found in Benin, one must admit that it excludes at the first sight social groups far away from the care and the most vulnerable, purveyors of maternal and infant mortality and death by accident of the public highway. Indeed, studies report a high children mortality caused by injury that could have been saved, most certainly, after adequate carefully giving free care . Similarly, 3.9% of patients with cerebral trauma die in hospitals because of the severity of the clinical picture at admission, the lack of adapted critical care services, and probably without IME possibility .…”
Section: Discussionmentioning
confidence: 99%
“…If this profile is superimposed on that found in Benin, one must admit that it excludes at the first sight social groups far away from the care and the most vulnerable, purveyors of maternal and infant mortality and death by accident of the public highway. Indeed, studies report a high children mortality caused by injury that could have been saved, most certainly, after adequate carefully giving free care . Similarly, 3.9% of patients with cerebral trauma die in hospitals because of the severity of the clinical picture at admission, the lack of adapted critical care services, and probably without IME possibility .…”
Section: Discussionmentioning
confidence: 99%
“…Suffla et al (2008) reported 85 homicide deaths due to strangulation per 100,000 population per year in Cape Town in 2001 and 67 per 100,000 per year in 2005 [ 28 ]. By comparison, a study in Dar es Salaam, Tanzania in 2005 by Outwater et al reported a homicide rate of 13 per 100,000 PYOs [ 29 ], while a 2007 injury mortality burden study by Mamady et al in Guinea reported a homicide rate of seven per 100, 000 PYOs [ 30 ]. A child homicide mortuary-based study in South Africa by Mathews et al in 2009 documented a homicide rate of 5.5 per 100,000 PYOs for children under the age of 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] With the right support, targeted and effective prevention campaigns can be waged in these nations to seriously address the global burn crisis. To date, this campaign was only waged in one region of one country.…”
Section: Discussionmentioning
confidence: 99%